Scientific and methodological basis for assessing the cointegration links of the contractor’s economic sustainability from the implementation of bim technology at all stages of the life cycle - Tsyfra, T. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to the analysis of the impact of the implementation of BIM technologies on the economic sustainability of construction enterprises operating during the war. The study is based on the study of co-integration dependencies between key economic parameters, such as fixed assets, working capital, human capital and net income. Scientifically based tools and methods are proposed for assessing the economic sustainability of enterprises, which are aimed at ensuring their adaptability, stability and long-term competitiveness. These tools and methods are integrated into the process of forming a strategy for the digital transformation of enterprises and cover all stages of the life cycle: from design to operation. The study substantiates the role of BIM technologies as a tool that ensures effective management of economic and organizational processes at the enterprise. The use of BIM contributes to the integration of information technologies into the production, financial and personnel processes of enterprises, which significantly increases their resistance to changes in the external environment. The article pays special attention to the analysis of such variables as the cost of fixed assets, working capital, the level of human capital utilization and their impact on the net income of enterprises. It was found that effective management of these indicators is critical for achieving economic stability. In addition, scientific and practical approaches to the integration of digital solutions into the construction industry are substantiated, which ensures the stable development of enterprises even in difficult external conditions. The study emphasizes the importance of integrating modern digital solutions, such as BIM, to ensure the effective functioning of enterprises in the construction industry. The use of BIM technologies creates opportunities for reducing risks, increasing the accuracy of management decisions and minimizing the negative consequences of economic instability. This contributes to achieving a balance between economic efficiency, quality of construction project implementation and compliance with external challenges. The practical results of the work can be used to create new approaches to assessing economic sustainability and developing long-term development strategies for construction enterprises. This will contribute to the sustainable development of the industry and ensure its competitiveness both at the national and international levels.